KOMPARASI KINERJA KEUANGAN BANK PERKREDITAN RAKYAT BERBASIS BEHAVIOURAL BENCHMARKING DAN PENGARUHNYA PADA PAJAK PENGHASILAN - Chandra, David; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
This study aims to determine whether the determination of the ratio of Behavioural Model Benchmarking by DGT for BPR sector in Badung are in accordance with the real conditions and to determine BPR financial performance effect to corporate income tax payments. The object of this study is BPRs operating in Badung regency with 36 samples for a 3 year period, namely 2011-2013, using purposive sampling techniques method. Data collected through secondary data. Analysis technique using the analysis of two different test sample average independent and simple linear regression analysis. The result of analysis of different test is a value Operating Profit Margin, pretax profit margin and net profit margin is greater than the ratio BPR Benchmark DJP, except the Corporate Tax rate to Turn Over Ratio value. The results of simple linear regression analysis is a positive influence on the financial performance of the corporate income tax payments.
Keywords: Compliance, Behavioural Model Benchmarking, Financial Ratios, Financial Performance, Corporate Income Tax Payments